Highly Active Antiretroviral Therapy and Increased Use of Contraceptives Among HIV-Positive Women During Expanding Access to Antiretroviral Therapy in Mbarara, Uganda - Andia, Irene; Kaida, Angela; Maier, Marissa; Guzman, David; Emenyonu, Nneka; Pepper, Larry; Bangsberg, David R.; Hogg, Robert S. (Andia, I., Kaida, A., Maier, M., Guzman, D., Emenyonu, N., Pepper, L., ... & Hogg, R. S. (2009). Highly active antiretroviral therapy and increased use of contraceptives among HIV-positive women during expanding access to antiretroviral therapy in Mbarara, Uganda. American journal of public health, 99(2), 340-347., 2009)
Objectives: We investigatedwhether the prevalence of contraceptive use among women who are HIV positive varied according to use of highly active antiretroviral therapy (HAART) in Mbarara, Uganda. Methods: We used data from a cross-sectional survey of 484 women who were HIV positive (18–50 years) and were attending Mbarara University’s HIV clinic, 45% of whom were receiving HAART.Multivariate logistic regression was used to investigate the association between HAART use and contraceptive use. Data were collected between November 2005 and June 2006. Results: Overall, 45% of the women were sexually active in the previous 3 months. Of these, 85% reported using contraceptive methods, with 84% reporting use of barrier contraceptive methods. Women receiving HAART were more than twice as likely to use contraceptive methods (adjusted odds ratio [AOR]=2.64; 95% confidence interval [CI]=1.07, 6.49) and more than 3 times as likely to use barrier contraceptive methods (AOR=3.62; 95% CI=1.54, 8.55) than were women not receiving HAART. Conclusions: Our findings support the need for increased attention to better integration of reproductive health and HIV and AIDS services for women who are HIV positive. (Am J Public Health. 2009; 99:340–347. doi:10.2105/AJPH.2007.129528)
Keywords: Antiretroviral Therapy; HIV-Positive Women; Uganda; HAART